U.S. Pavilion Entrance (Seville Enterprises, Inc.)
U.S. Pavilion spread under a sweeping canopy that seems to grow out of the natural contours of the land. Open at the top, the canopy does not quite touch the ground, giving an open air aspect to the series of exhibits.